Difference Between Written And Spoken Language - Khilola Sadullaeva Azamjon kizi (Peerian Journals Publishing, 2025)
In this article we can see the differentiation of two forms of language that is, written and spoken language. Key features of language forms are deeply discussed. It's argued that anything which is published in print can be written language and it's saved for a long time. However, oral language is kept for short period. On the other hand, certain types of writing are more similar to speech than others. It is also analyzed that mimes and gestures can be used in oral language but in written form they are expressed with punctuation marks. It is explained that intonation, emotional expressions , tembre and such kind of things are used only spoken language.
Keywords: spoken language; written language; linguistic nuances; context